Strategi Wartawan Foto Dalam Menentukan Sudut ‎Pengambilan Foto Sepakbola - Mugits Burhanudin, Ahmad Abdul; suherdiana, dadan; Maarif, Abdul Aziz (Annaba: Jurnal Ilmu Jurnalistik, 2021)
This paper aims to of this research is to find out how the photographer's role is in determining the angle of shooting published on the news portal on the Persib Bandung website. This research is the theory or method of EDFAT photography. The research method used is the phenomenological method with data collection techniques through interviews. The results of the study show that the Persib photographer's understanding of angles for sports photos is divided into several derivatives, namely basic understanding, defined angle criteria, and copyright on photographs produced by photographers. The informant also interpreted that the angle of the photo is the angle of the camera placement which can manipulate the reader's feelings if the angle variation is used for an object and the moment is right. Furthermore, on the experience of working on angles, the photographer will plan a strategy and then apply it in the field.